OUTCOME OF BALLOON VALVULOPLASTY IN CHILDREN WITH PULMONARY STENOSIS - SINGLE CENTER EXPERIENCE - Tausif Ahmed; Ijaz Hussain; Saadia Ilyas; Syed Sajid Hussain Shah; Yasir Rehman; Asadullah Khan; Muhammad Zeeshan Haroon (Journal of Ayub Medical College Abbottabad, 2021)
Background: Pulmonary valve stenosis (PS) is common congenital heart disease in children and patient can present with cyanosis, chest pain, dyspnea and failure with severe form. The objective of this study was to enlighten the short outcome of balloon pulmonary valvuloplasty in children with severe pulmonary stenosis. Methods: This cross sectional observational study was done in paediatric cardiology department of Lady Reading Hosptial, Peshawer form June 2019 to December 2020 over 1.5 years. Children aged 6 months to 16 years of either sex diagnosed as case of severe stenosis with doming pulmonary valve and having symptoms of chest pain and dysnea on exeration and pregradient pressure of 64 mm Hg or more on echocardiography were included. Patients were interviened with ballon-valvuloplasty. Outcome was taken as discharge from hospital with complications after procedure if any. Patients were followed up for 3 months. Data including age, sex, pre cath echocardiography, cath pulmonary valve annulus, post ballooning pulmonary valve (PV) gradient, PV gradient on echocardiography after intervention and follow up gradient on echocardiography at three months was documented. Data was analyzed by SPSS 20. Chi square test and paired T - Test was applied where required. Results were taken as significant with p value <0.05. Results: There were 51 patients, 35 (68.6%) male and 16 (31.4%) female. Mean age was 8.35±4.93 years. Mean pre cath gradient across the pulmonary valve on echocardiography was 109.14±31.44 mm Hg. Post intervention mean pressure gradient across PV was 32.41±11.49 mm Hg. Pulmonary valve annulus on echocardiography before intervention ranged from 7 to 25 mm with mean of 14.67±3.79 mm. There was no complication in majority (82.4%) of patients. Mild PR was in 5 (9.8%) patients. There was significant relationship between pre and post intervention pressure gradient across PV valve with p value of <0.001. Conclusion: balloon pulmonary valvuloplasty in one of the safest intervention for PS in children with few complications. Background: Pulmonary valve stenosis (PS) is common congenital heart disease in children and patient can present with cyanosis, chest pain, dyspnea and failure with severe form. The objective of this study was to enlighten the short outcome of balloon pulmonary valvuloplasty in children with severe pulmonary stenosis. Methods: This cross sectional observational study was done in paediatric cardiology department of Lady Reading Hosptial, Peshawer form June 2019 to December 2020 over 1.5 years. Children aged 6 months to 16 years of either sex diagnosed as case of severe stenosis with doming pulmonary valve and having symptoms of chest pain and dysnea on exeration and pregradient pressure of 64 mm Hg or more on echocardiography were included. Patients were interviened with ballon-valvuloplasty. Outcome was taken as discharge from hospital with complications after procedure if any. Patients were followed up for 3 months. Data including age, sex, pre cath echocardiography, cath pulmonary valve annulus, post ballooning pulmonary valve (PV) gradient, PV gradient on echocardiography after intervention and follow up gradient on echocardiography at three months was documented. Data was analyzed by SPSS 20. Chi square test and paired T - Test was applied where required. Results were taken as significant with p value <0.05. Results: There were 51 patients, 35 (68.6%) male and 16 (31.4%) female. Mean age was 8.35±4.93 years. Mean pre cath gradient across the pulmonary valve on echocardiography was 109.14±31.44 mm Hg. Post intervention mean pressure gradient across PV was 32.41±11.49 mm Hg. Pulmonary valve annulus on echocardiography before intervention ranged from 7 to 25 mm with mean of 14.67±3.79 mm. There was no complication in majority (82.4%) of patients. Mild PR was in 5 (9.8%) patients. There was significant relationship between pre and post intervention pressure gradient across PV valve with p value of <0.001. Conclusion: balloon pulmonary valvuloplasty in one of the safest intervention for PS in children with few complications.